SOCIAL AND CULTURAL ADAPTATION OF LOCAL COMMUNITIES TO ENVIRONMENTAL CHANGES DUE TO TOURISM IN CANGGU VILLAGE - PRITA FARAH DINA MAYANGSARI; MUTIMMATUS SA’ADAH; NASYWA AZZAHRA; SALSABILA SAYU RISTY; SUGIANTORO (Innovare Journal of Social Sciences, 2025)
This article aims to analyze how the local community of Canggu village adapts socially and culturally to environmental changes caused by the rapid development of tourism. Canggu village, which was originally an agricultural area with a strong agricultural system and traditional values, has undergone a major transformation along with the increasing conversion of agricultural land into tourist areas, such as villas, restaurants, and entertainment centers. This change not only affects the economic aspect but also has a significant impact on the social order, cultural values, and environmental conditions. This study uses a qualitative approach with a descriptive method, through in-depth interviews and direct observation of local communities, traditional leaders, business actors, and the younger generation. The results of the study show that the Canggu community is able to maintain its cultural identity through the preservation of traditional ceremonies, the spirit of mutual cooperation, and community-based environmental management, despite being faced with challenges, such as cultural commodification, pollution, and development pressures. The adaptation strategies carried out reflect an active and dynamic process in accordance with the theory of socio-cultural adaptation and Parsons’ social systems theory, which emphasizes the importance of integration between tradition and modernity. This article concludes that despite the great challenges tourism brings, the Canggu community shows strong cultural and social resilience. Therefore, a more participatory and sustainable tourism development policy is needed so that the balance between economic growth, cultural preservation, and environmental sustainability can continue to be maintained.